PERANCANGAN UI/UX DELIVERY MOBILE APP DENGAN METODE DESIGN THINKING DAN USABILITY SCALE - Saddyah, Trie Meutia; Saragih, Saut Pintubipar (Universitas Putera Batam, 2024)
Delivery services are one of the sectors in the business world that is influential in business development, along with the increasing behaviour of people in online shopping. With significant growth in the courier and delivery service sector, many individuals or the courier and delivery service industry are trying to adopt technology that can support the ease of the delivery process with effective management for use. In general, the issue encountered when designing an application is that it does not match the needs of users, resulting in the program failing to achieve its goal. One method that is considered capable of solving these problems is the design thinking method. This research discusses the UI/UX Design of Delivery Mobile App implementing the design thinking approach with the aim of providing smooth delivery of goods. The use of the Delivery Mobile App is aimed at senders to improve their smoothness and convenience in the process of sending goods and the interface that suits the needs of the sender. Prototype testing using the System Usability Scale (SUS) yielded a score of 82 and an adjective rating of 'B' or 'Excellent'.